(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article examines the peculiarities of the spinal cord and the concept of "spinal cord membranes" in children. It discusses their anatomical development, functional significance, and potential clinical consequences. By analyzing comprehensive literature, the study focuses on understanding the maturation process, methods used to study pediatric spinal cord structures, and the impact of these findings on pediatric neurology.